Diagnostic accuracy of pocket-size lung ultrasound for etiological definition of pneumonia and surveillance of complications in children hospitalized: a prospective diagnostic cohort study - Monteiro, Sara; Tavares, Teresa; Salazar, Luís; Coelho, Filipa; Carvalho, João; Barbosa, Telma; Reis, Maria G.; Morais, Lurdes; Ramos, Ana; Ferreira-Magalhães, Manuel (International Journal of Clinical Trials, 2024)
Background: Pneumonia, the leading infectious cause of death in children worldwide, often requires a chest radiograph (CXR) for diagnosis, involving radiation exposure. Point-of-Care Ultrasound (POCUS) offers a radiation-free alternative and, specifically the pocket-size variant, enhances convenience at the patient’s bedside. While evidence supports ultrasound’s accuracy in detecting community-acquired pneumonia (CAP) in children comparable to CXR, few studies have explored its ability to distinguish pneumonia etiology, especially utilizing pocket-size POCUS devices. Methods: In this prospective diagnostic cohort study conducted over a year in a tertiary pediatric referral center, we aim to assess the diagnostic accuracy of a pocket-size POCUS device compared to CXR for determining the etiology of CAP in pediatric patients (aged >6 months and <18 years). At least 76 participants diagnosed with CAP will undergo independent POCUS examinations at various intervals, complemented by CXRs when necessary, independently classified by a third investigator. The General Electrics Vscan AirTM®, featuring Bluetooth connectivity to smartphone/tablet, will be employed for POCUS. Data collection will include systematized POCUS and CXR descriptions, alongside sociodemographic, clinical, and therapeutic variables. Statistical analysis using SPSS® version 28 will evaluate the diagnostic accuracy of the POCUS device. Conclusions: This trial’s outcomes hold significant promise in unveiling unknown data about the diagnostic accuracy of pocket-size POCUS for pediatric CAP etiological diagnosis. Utilizing a device meeting technical recommendations, featuring a dual-headed probe and Bluetooth connectivity, this study has the potential to bring innovation to clinical practice, improving patient care and creating scientific value. Trial Registration Number: NCT06296693.